Local implementation of a national program: The National Estuary Program response following the Deepwater Horizon oil spill in the Gulf of Mexico. (January 2018) - Greening, Holly; Swann, Roberta; St. Pé, Kerry; Testroet-Bergeron, Susan; Allen, Ray; Alderson, Mark; Hecker, Jennifer; Bernhardt, Sarah P.
Abstract: The US Environmental Protection Agency's National Estuary Program (NEP) was established in 1987 under the Clean Water Act to improve the water quality and ecological integrity of estuaries of national importance. There are twenty-eight individual local programs in the NEP, covering watersheds in eighteen coastal states and Puerto Rico. Each is charged with bringing together citizens, scientists, businesses and government officials to collaboratively solve environmental problems and promote healthy, vibrant communities. Decisions are based on sound science and actions are implemented using adaptive management strategies. With expertise and comprehensive local networks, each local NEP is able to serve as a foundation for addressing emerging environmental problems, including hazardous events, such as oil spills and hurricanes. An example is the unique role that the NEPs along the Gulf of Mexico played during the Deepwater Horizon oil spill. Immediately following the spill, while federal and state agencies and oil industry experts worked to contain the spill, local communities were faced with conflicting and confusing information about the activities. The NEPs provided credible and continuously-updated information to local communities; led major outreach efforts in their communities concerning the event; and served as conduits for scientific information and data to local, state and federal agency scientists and officials. Gulf NEPs continued to facilitate community involvement and provide long-term assistance to the state and federal recovery efforts along the Gulf, and are now coordinating community-based restoration efforts to assist in the long-term recovery of the resources and communities along the Gulf coast. Highlights: Local implementation of National Estuary Programs fill gaps in emergency response. Gulf NEPs led outreach efforts in their communities during a major oil spill. Gulf NEPs provide a science-based, cooperative network supporting Gulf recovery. Ongoing NEP monitoring networks provided baseline data for damage assessment. Role of NEPs to build science-based consensus will continue to be a strength.